2022
DOI: 10.3389/fmicb.2022.877483
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Interactions — Underexplored Links Between Public Health Relevant Bacteria and Protozoa in Coastal Environments

Abstract: The co-existence of bacteria and protozoa in aquatic environments has led to the evolution of predation defense mechanisms by the bacteria. Some of the predation-resistant bacteria (PRB) are also pathogenic to humans and other mammals. The links between PRB and protozoa in natural aquatic systems are poorly known, but they are important in predicting outbreaks and determining the long-term consequences of a contamination event. To elucidate co-occurrence patterns between PRB (16S rRNA) and bacterivorous protoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Samplings were conducted by following the course of four freshwater inlets towards the brackish water of the Gulf of Bothnia, northern Baltic Sea. Four surface water samples were collected (0.5 m depth) once in a month in these four bays during the summer period (June to September) in 2018 (Eriksson et al 2022 ). In addition, samples from two offshore sites were also collected in each month (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Samplings were conducted by following the course of four freshwater inlets towards the brackish water of the Gulf of Bothnia, northern Baltic Sea. Four surface water samples were collected (0.5 m depth) once in a month in these four bays during the summer period (June to September) in 2018 (Eriksson et al 2022 ). In addition, samples from two offshore sites were also collected in each month (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All water samples were collected in sterile sampling bottles, then transported to the laboratory and stored in the dark at 4 °C. Physicochemical properties of samples were measured (Eriksson et al 2022) and included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…With the aim to further investigate biotic interactions and, in particular, potential parasitic-host associations, co-occurrence network was constructed. In parallel to this study, 18S V6-V8 rRNA gene sequences have been generated using the same samples (Eriksson et al 2022) and the subset of that dataset was used to assess potential host–parasitic(saprotrophic) associations in our bay samples (n = 40). Absolute read counts were used for the network analysis because previous studies have shown that relative abundance data suffer from apparent correlations which lower specificity of association networks (Berry & Widder 2014, Meng et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations